Validation of a dry sliding wear simulation method for wastegate bearings in automotive turbochargers. (March 2021) - Schmidt, Adrian A.; Plánka, Jakub; Schmidt, Timo; Grabherr, Oliver; Bartel, Dirk
Abstract: A simulation model to determine dry sliding wear behavior of wastegate bearings is validated by comparison with experimental results. The wear results of a pin-on-plate tribometer running at 300 ∘ C are used to define global wear coefficients. These serve as input information for a FEM simulation which is able to calculate local wear progress in the model. The simulation results show good correlation with the experiment for the general wear shape and the local wear depth. Volume gain is observed on one of the contact partners due to material transfer. This effect is not included in the simulation model and thus cannot be reproduced. Highlights: Tribometer test at elevated temperature with austenitic steels. Advanced wear simulation method for dry sliding based on finite elements. Detailed comparison of test and simulation results. High correlation between material removal in simulation and experiment.